Mouse spermatocytes express CYP2E1 and respond to acrylamide exposure. - Belinda J Nixon; Aimee L Katen; Simone J Stanger; John E Schjenken; Brett Nixon; Shaun D Roman (PLoS ONE)
Metabolism of xenobiotics by cytochrome P450s (encoded by the CYP genes) often leads to bio-activation, producing reactive metabolites that interfere with cellular processes and cause DNA damage. In the testes, DNA damage induced by xenobiotics has been associated with impaired spermatogenesis and adverse effects on reproductive health. We previously reported that chronic exposure to the reproductive toxicant, acrylamide, produced high levels of DNA damage in spermatocytes of Swiss mice. CYP2E1 metabolises acrylamide to glycidamide, which, unlike acrylamide, readily forms adducts with DNA. Thus, to investigate the mechanisms of acrylamide toxicity in mouse male germ cells, we examined the expression of the CYP, CYP2E1, which metabolises acrylamide. Using Q-PCR and immunohistochemistry, we establish that CYP2E1 is expressed in germ cells, in particular in spermatocytes. Additionally, CYP2E1 gene expression was upregulated in these cells following in vitro acrylamide exposure (1 µM, 18 h). Spermatocytes were isolated and treated with 1 µM acrylamide or 0.5 µM glycidamide for 18 hours and the presence of DNA-adducts was investigated using the comet assay, modified to detect DNA-adducts. Both compounds produced significant levels of DNA damage in spermatocytes, with a greater response observed following glycidamide exposure. A modified comet assay indicated that direct adduction of DNA by glycidamide was a major source of DNA damage. Oxidative stress played a small role in eliciting this damage, as a relatively modest effect was found in a comet assay modified to detect oxidative adducts following glycidamide exposure, and glutathione levels remained unchanged following treatment with either compound. Our results indicate that the male germ line has the capacity to respond to xenobiotic exposure by inducing detoxifying enzymes, and the DNA damage elicited by acrylamide in male germ cells is likely due to the formation of glycidamide adducts.